2016
DOI: 10.1016/j.envpol.2016.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the developmental and neurotoxicity of the mosquito control larvicide, pyriproxyfen, using embryonic zebrafish

Abstract: In 2014, as an attempt to address the Zika health crisis by controlling the mosquito population, Brazil took the unprecedented action of applying a chemical larvicide, pyriproxyfen, to drinking water sources. The World Health Organization has established an acceptable daily intake of pyriproxyfen to be 100 micrograms per kg of body weight per day, but studies have demonstrated that at elevated doses (>5000 mg/kg), there are adverse effects in mice, rats and dogs. To better understand the potential developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 13 publications
3
47
0
1
Order By: Relevance
“…This observation is consistent with the half maximal effective concentration (EC 50 ) of 1.6 μg/ml (i.e. 5 μM) that has been found in a previous study in zebrafish37. Consistently, we also treated embryos with extremely high doses of pyriproxyfen, concentrations ranging from 10 to 100 μg/ml, and noticed a high level of toxicity leading to death in 100% of the embryos as early as 2 dpf ( p  < 0.0001, Logrank test, N = 2, n = 20; Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with the half maximal effective concentration (EC 50 ) of 1.6 μg/ml (i.e. 5 μM) that has been found in a previous study in zebrafish37. Consistently, we also treated embryos with extremely high doses of pyriproxyfen, concentrations ranging from 10 to 100 μg/ml, and noticed a high level of toxicity leading to death in 100% of the embryos as early as 2 dpf ( p  < 0.0001, Logrank test, N = 2, n = 20; Fig.…”
Section: Resultssupporting
confidence: 93%
“…All the experimental protocols were performed under the approval of the vertebrate animal welfare assurance from the Institutional Animal Care and Use Committee (IACUC) for the use of adult zebrafish (approved on 2015/08/31). The elavl3, nestin and gfap transgenic lines were previously generated as described3743 and are routinely maintained in our fish facility at the CRCHUM.…”
Section: Methodsmentioning
confidence: 99%
“…As such, a repertoire of zebrafish-based behavioral assays across multiple life-stages (including adulthood) have been developed over the last 10–15 years (Bang et al, 2002; Brockerhoff et al, 1995; Egan et al, 2009; Kokel et al, 2010). Although different forms of larval and adult zebrafish locomotion have been leveraged within behavioral assays, spontaneous activity (tail contraction) – a behavior that occurs from late-segmentation (~17–19 hours post-fertilization, hpf) through early-pharyngula (~27–29 hpf) – represents an early, primitive form of motor activity within zebrafish embryos, providing a potential readout for rapid identification of neuroactive chemicals (Kokel et al, 2010; Raftery et al, 2014; Reif et al, 2015; Truong et al, 2016). Although previous studies have explored the biological basis of this behavior (Knogler et al, 2014; Knogler and Drapeau, 2014; Saint-Amant and Drapeau, 2001, 2000), it remains unclear whether spontaneous activity is responsive only to certain compounds with specific mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies, both using Zebrafish, have addressed the question of whether PPF could be implicated in microcephaly, each producing contradictory results (Dzieciolowska et al, 2017; Truong et al, 2016). One study (Truong et al, 2016) demonstrated that PPF induces adverse morphological changes including craniofacial defects in zebrafish at 5.2 μM (1.66 mg/L) - EC50. In the behavioral test PPF at 6.4μM (2 mg/L) and 64μM (20mg/L) significantly reduced the mobility of the zebrafish larvae compared to control animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the behavioral test PPF at 6.4μM (2 mg/L) and 64μM (20mg/L) significantly reduced the mobility of the zebrafish larvae compared to control animals. The authors concluded that the developmental toxicity of PPF may not be limited only to insects (Truong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%